2016
DOI: 10.2147/nss.s100271
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fabric for sleepwear and bedding on sleep at ambient temperatures of 17°C and 22°C

Abstract: The fibers used in clothing and bedding have different thermal properties. This study aimed to investigate the influences of textile fabrics on sleep under different ambient temperature (Ta) conditions. Seventeen healthy young participants (ten males) underwent nine nights of polysomnography testing including an adaptation night. Participants were randomized to each of the three binary factors: sleepwear (cotton vs wool), bedding (polyester vs wool), and Ta (17°C vs 22°C with relative humidity set at 60%). Ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…An increase of N3 (%) indicates deeper sleep, i.e., better sleep quality. Similar to this study, Shin et al [9] reported that N3 (%) increased, while N2 (%) decreased, at a relatively low temperature when wearing wool sleepwear com-pared to cotton sleepwear, indicating improved sleep quality. Future studies aiming to replicate our results should include more participants; the lack of significant differences in objective sleep variables in our study may have been due to the small sample size.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An increase of N3 (%) indicates deeper sleep, i.e., better sleep quality. Similar to this study, Shin et al [9] reported that N3 (%) increased, while N2 (%) decreased, at a relatively low temperature when wearing wool sleepwear com-pared to cotton sleepwear, indicating improved sleep quality. Future studies aiming to replicate our results should include more participants; the lack of significant differences in objective sleep variables in our study may have been due to the small sample size.…”
Section: Discussionsupporting
confidence: 87%
“…One study showed that "body-pressing sleepwear" resulted in making the rise of skin temperature and the decline of rectal temperature less, which could affect circadian rhythm [7]. Researchers also found that among several materials (e.g., wool, cotton, and polyester) the insulating properties of wool sleepwear pro-Preliminary Study on the Effect of Sleepwear on Objective and Subjective Sleep Quality moted sleep and improved sleep quality [8,9]. Sleepwear is not only used to preserve body temperature, but also to control it.…”
Section: Introductionmentioning
confidence: 99%
“…Some sleep issues may be mitigated by choosing an appropriate pillow type, e.g., with an appropriate pillow neck and side height [24], and sleepwear fabric type, e.g., sleeping in wool promoted improved sleep [25,26]. The food type consumed may also help to promote sleep onset, e.g., a high glycemic index meal shortened sleep onset compared to a low glycemic index meal [27].…”
mentioning
confidence: 99%
“…Dry wool fiber absorbs moisture up to about 35% of its dry weight in saturated air, whereas cotton can absorb around 24% and polyester below 1% 17. A previous study investigated the influence of sleepwear (cotton vs wool) and bedding type (polyester vs wool) on the sleep quality of healthy young participants 18. Although no effect on sleep of bedding type was observed, sleep onset latency (SOL) was significantly shortened when sleeping in wool sleepwear with less stage 3 sleep observed for wool than for cotton.…”
Section: Introductionmentioning
confidence: 98%